3D parametric human modeling for warp-knitted seamless garment. Issue 4 (3rd August 2015) - Dong, Zhijia; Jiang, Gaoming; Wu, Zhiming; Cong, Honglian
Abstract : Purpose: – The purpose of this paper is to develop a parametric design method for 3D human bodies to be used in computer-aided style design and the 3D presentations of warp-knitted seamless garment. Design/methodology/approach: – In order to obtain 3D human bodies of different sizes, all of which have been based on anthropometric measurement, a human body model template was constructed by importing vertices and facets information in an OBJ model file which had been exported from POSER. A parametric model was then established by extracting feature information from the template model using a method combining 3D geometry analysis and human semantic analysis; this information included the template model's feature points and measurements. By applying a mesh deformation method, based on the radius basis function interpolation, to the template model, different size human bodies were then generated according to user-specific anthropometric measurements. Findings: – The test results validated the method presented in this paper as a useful and effective approach to generate diffident size human models from a template model by modifying anthropometric measurements, which establishes a foundation for the style design and 3D presentations of warp-knitted seamless garments. Originality/value: – This paper provides parametric design methods for generating bodies of varying size according to different anthropometric measurements in the 3D domain, which is the basis of style design and 3D presentation for warp-knitted seamless garments.